Knowledge and level of adherence to home exercise program among Malaysian caregivers of children with Cerebral Palsy - Lee, Fei Sean; Rajkumar Krishnan, Vasanthi; Siti Noorhaslina, Mohd Zaidi (INTI International University, 2021)
Background: Cerebral palsy (CP) is one of the most prevalent disorders that severely affected the motor function in young children worldwide. It is a condition that requires life-long care and the efforts needed depends on the severity & complexity of the children. To deliver proper care to the CP child according to their needs, caregivers must have fundamental and adequate knowledge about CP. A caregiver plays a crucial role in encouraging and providing assistance to CP children to achieve their highest potential. Exercise programs in CP are lifelong activities prescribed for home, and it varies from children to children according to their disabilities. Objectives: To explore caregivers' knowledge of cerebral palsy and the level of caregivers' adherence to home exercise programs. Method: A cross-sectional survey was conducted with purposive sampling strategy to include the caregivers of CP children from a Non-Governmental Organization for spastic Cerebral Palsy children. A validated self-administered questionnaire was given to the caregivers after they consented to participate in the study. The results were analyzed using descriptive analysis. Result: 57 caregivers participated in the study survey voluntarily. There are only 52.6% of caregivers answered the questions on knowledge of CP correctly. 45% of caregivers adhered to the home exercise program that physiotherapist implements. Conclusion: Caregivers of children with cerebral palsy have a low level of knowledge and low adherence in performing a home exercise program. Empowering the caregivers and creating better awareness of the condition and treatment adherence need to be encouraged.